Small nucleic acid drugs-the dawn of functional cure of chronic hepatitis B - Zhang, Lu; Cao, Yu; Zhuang, Sijing; Sun, Jingjing; Tong, Qiao; Xi, Jianjun; Liu, Shourong; Zhuang, Rangxiao (Frontiers in Pharmacology, 2025)
Chronic hepatitis B (CHB), a chronic liver infectious disease, results from persistent hepatitis B virus (HBV) infection lasting over 6 months. It has become a substantial global public health burden. CHB is often manifested by concomitant hepatic biochemical abnormalities, and/or notable inflammatory necrosis, and/or liver histological fibrosis. If left uncontrolled, CHB can progress to severe liver diseases and may even lead to death. Although currently approved therapeutic agents can effectively suppress viral replication and, to a certain extent, reduce related complications, their ineffectiveness in targeting covalently closed circular DNA (cccDNA) fundamentally restricts their potential to achieve a clinical cure. In recent years, research focused on attaining a functional cure for CHB has been on the rise. Drugs with different targeting mechanisms and diverse therapeutic strategies have rendered a clinical cure for CHB a possibility. Among these, emerging small nucleic acid drugs show great promise, exhibiting high potential for achieving a sustained functional cure. In this review, we systematically investigate the unique structure of the HBV genome. Moreover, we delve into the classification, mechanisms of action, and pathways for small nucleic acid drugs used in CHB treatment to achieve a functional cure. Additionally, we analyze some challenges encountered in the development of these drugs and propose corresponding solutions. Furthermore, we discuss current clinical studies and combination therapies involving small nucleic acid drugs for CHB treatment.